Pitfalls Associated with Discriminating Mixed-Species Biofilms by Flow Cytometry - Tânia Grainha; Andreia P. Magalhães; Luís D. R. Melo; Maria O. Pereira (MDPI AG, 2020)
Since biofilms are ubiquitous in different settings and act as sources of disease for humans, reliable methods to characterize and quantify these microbial communities are required. Numerous techniques have been employed, but most of them are unidirectional, labor intensive and time consuming. Although flow cytometry (FCM) can be a reliable choice to quickly provide a multiparametric analysis, there are still few applications on biofilms, and even less on the study of inter-kingdom communities. This work aimed to give insights into the application of FCM in order to more comprehensively analyze mixed-species biofilms, formed by different Pseudomonas aeruginosa and Candida albicans strains, before and after exposure to antimicrobials. For comparison purposes, biofilm culturability was also assessed determining colony-forming units. The results showed that some aspects, namely the microbial strain used, the morphological state of the cells and the biofilm matrix, make the accurate analysis of FCM data difficult. These aspects were even more challenging when double-species biofilms were being inspected, as they could engender data misinterpretations. The outcomes draw our attention towards the need to always take into consideration the characteristics of the biofilm samples to be analyzed through FCM, and undoubtedly link to the need for optimization of the processes tailored for each particular case study.